Online adaptive MR-guided radiotherapy for rectal cancer; feasibility of the workflow on a 1.5T MR-linac: clinical implementation and initial experience. (January 2021) - Intven, M.P.W.; de Mol van Otterloo, S.R.; Mook, S.; Doornaert, P.A.H.; de Groot-van Breugel, E.N.; Sikkes, G.G.; Willemsen-Bosman, M.E.; van Zijp, H.M.; Tijssen, R.H.N.
Highlights: MR-guided radiotherapy for rectal cancer on a 1.5T MR-linac is feasible. An online adaptive workflow takes about 48 min each fraction. Treatment of rectal cancer on the 1.5T MR-linac is well tolerated by patients. This workflow holds promise for margin reduction. Abstract: Background and purpose: Daily online adaptation of the clinical target volume (CTV) using MR-guided radiotherapy enables margin reduction of the planning target volume (PTV). This study describes the implementation and initial experience of MR-guided radiotherapy on the 1.5T MR-linac and evaluates treatment time, patient compliance, and target coverage, including an initial assessment of margin reduction. Materials and methods: Patients were treated on a 1.5T MR-linac (7MV, FFF). At each fraction a 3D T2 weighted (T2w) MR-sequence was acquired on which the CTV was adapted after a deformable registration of the contours from the pre-planning CT scan. Based on the new contours a full online replanning was done after which a new 3D T2w MR-sequence was acquired for position verification. A 5 field Intensity Modulated Radiotherapy (IMRT) plan was delivered. Results: Forty-three patients with rectal cancer were treated with 25 Gy in 5 fractions of which 18 with reduced margins. In total, 204 of 215 fractions were delivered on the MR-linac all of which obtained a clinically acceptable treatment plan. Median in-room time per fraction was 48 min (interquartile range 8). No fractions were canceled or interrupted because of patient intolerance. CTV coverage after margin reduction was good on all post-treatment scans but one due to passing gas. Conclusion: MR-guided radiotherapy using daily full online recontouring and replanning on a 1.5T MR-linac for rectal cancer is feasible and currently takes about 48 min per fraction.